2022
DOI: 10.3390/ijms23052565
|View full text |Cite
|
Sign up to set email alerts
|

Safety of G2-S16 Polyanionic Carbosilane Dendrimer as Possible HIV-1 Vaginal Microbicide

Abstract: The UNAIDS objective for 2020 was 500,000 new HIV-1 infections per year; however, the latest annual reported data confirmed 1.7 million new HIV-1 infections in that year. Those data evidences the need for new prevention strategies and prophylactic treatments. This prevention crisis occurred in spite of the knowledge and availability of efficient prevention strategies. The G2-S16 is a microbicidal polyanionic carbosilane dendrimer currently being tested for topical vaginal application, which has been shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The application of G2‐S16‐FITC to the epithelial vaginal tissue of BALB/c mice confirmed that this family of dendrimers crosses this barrier reaching the circulatory system. The study of organs and other biochemical data confirmed that this anionic dendrimer, alone or combined with antiretroviral drugs (tenofovir and emtricitabine), is a promising system to develop an effective microbicide against HIV‐1 infection (Martin‐Moreno et al, 2022; I. Rodríguez‐Izquierdo, Sepúlveda‐Crespo, et al, 2022).…”
Section: Pharmaceutical Applications Of Carbosilane Dendritic Moleculesmentioning
confidence: 79%
“…The application of G2‐S16‐FITC to the epithelial vaginal tissue of BALB/c mice confirmed that this family of dendrimers crosses this barrier reaching the circulatory system. The study of organs and other biochemical data confirmed that this anionic dendrimer, alone or combined with antiretroviral drugs (tenofovir and emtricitabine), is a promising system to develop an effective microbicide against HIV‐1 infection (Martin‐Moreno et al, 2022; I. Rodríguez‐Izquierdo, Sepúlveda‐Crespo, et al, 2022).…”
Section: Pharmaceutical Applications Of Carbosilane Dendritic Moleculesmentioning
confidence: 79%